How muslim women empower themselves through active participation in Islam in Indonesia? - Bintari, Dini Rahma (Jurnal Psikologi Islam, 2019)
This qualitative study explored how women empower themselves through active participation in Islam in Indonesia. Twenty-four women from eight different cities in Indonesia, who were active more than five years in Muslim women organizations, were selected for semi-structured interview. The ages ranged from 25 to 53 years, and most of them were married with children and had completed bachelor degrees. Eleven women were from Salimah organization, eight from Aisyiah/Nasyiatul Aisyiah, and five from Muslimat/Fatayat NU. The interview data were analyzed using thematic analysis. Five themes were elicited from the interview: concept and domains of empowerment, affective aspects of empowerment, role of Islamic religious values and rituals in empowerment, social environment influences on women’s empowerment, influences of Muslim women’s organizations and member empowerment. The women who had longer membership showed that transcendence as dominant motivation. Overall results showed that transformation and empowerment were acquired through activities in the Muslim women’s organizations. Keywords: active participation, empowerment, Islam, women